2020
DOI: 10.4084/mjhid.2020.053
|View full text |Cite
|
Sign up to set email alerts
|

Severe autoimmune hemolytic anemia in Covid-19 infection

Abstract: xx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 12 publications
5
27
0
Order By: Relevance
“…None of the previous reports involving newborns born to SARS-CoV-2 positive mothers describe hemolytic anemia, but there are reports of autoimmune hemolytic anemia in adults with SARS-CoV-2 infection, presumably caused by the cytokine storm or through molecular mimicry. [14][15][16][17] Most of the reported cases of SARS-CoV-2 infection associated with hemolytic anemia had an underlying condition predisposing to hemolysis such as spherocytosis, G-6-PD deficiency, or malignancy 18 similar to our cases.…”
Section: Discussionsupporting
confidence: 78%
“…None of the previous reports involving newborns born to SARS-CoV-2 positive mothers describe hemolytic anemia, but there are reports of autoimmune hemolytic anemia in adults with SARS-CoV-2 infection, presumably caused by the cytokine storm or through molecular mimicry. [14][15][16][17] Most of the reported cases of SARS-CoV-2 infection associated with hemolytic anemia had an underlying condition predisposing to hemolysis such as spherocytosis, G-6-PD deficiency, or malignancy 18 similar to our cases.…”
Section: Discussionsupporting
confidence: 78%
“…Comparison of patients who were cured (meeting standards of hospital discharge) and those who were not cured showed that anemia and other factors were not associated with healing of COVID-19 during following-up (Table 4). thalassemia, 18 autoimmune hemolytic anemia, 19 and megaloblastic anemia, 20 have been recently reported. However, little proportion of attention was paid on common anemia in COVID-19 patients.…”
Section: Differences In Covid-19 Patients With Various Disease Conditmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), which is caused by a newly discovered positive-sense singlestranded RNA virus that termed SARS-CoV-2, has become an extensive pandemic worldwide since it is rstly broken out in Wuhan, Hubei Province in December 2019. [1][2] As of July 26, 2020, there were approximately 15,785,000 COVID-19 con rmed cases that existed in 215 countries or regions around the world, and nearly half of them were distributed in America, Brazil and India.…”
Section: Introductionmentioning
confidence: 99%
“…For HCT% Mean ± SD in mild stages of the disease were significantly higher (P1 < 0.001) compared to sever stage (40.69 ± 5.22 vs 35.87 ± 8.71% respectively), and the median were (43 vs 36.5 respectively). There are several reported cases where autoimmune hemolytic anemia occurred during the worsening of symptoms of Covid-19 infection [34][35][36]. Reduced Hb level with the associated reduction of oxygen carrying capacity of the blood together with CT diagnosed lung parenchymal pathology explains the significant dyspnea associated with increased disease severity.…”
Section: Discussionmentioning
confidence: 99%